ANALISIS STRATEGI KOMUNIKASI PEMASARAN (Studi Kasus Strategi Komunikasi Pemasaran Merchandise di Kedai Digital 8 Solo) - Doni Mardiyanto; Giarti Giarti (ITB AAS INDONESIA Surakarta, 2019)
This study aims to determine the marketing communication strategy in Kedai Digital 8 Solo in increasing sales of merchandise products. This study uses qualitative descriptive methods, namely research that seeks to describe or describe the object under study based on facts in the field. Data presented using primary data, secondary data through structured interviews, observations, and documentation relating to this study. The data analysis technique used in this study is qualitative data analysis. The results of this study indicate that the marketing communication strategy applied by Kedai Digital 8 Solo is advertising (advertising) and direct marketing (direct marketing). Advertising uses brochure media, banners / MMT and through social media. While direct marketing is done using media letters / proposals submitted to individuals and companies / agencies. Of the two strategies implemented, advertising through social media (online) is more routine because it is considered more effective and efficient. While direct marketing through media letters / proposals is carried out periodically at least once a year even rarely. Keywords: communication strategy, marketing, advertising